APAKAH BANK SYARIAH BERBEDA DENGAN BANK KONVENSIONAL? (KAJIAN FENOMENOLOGI) - Tyagita Winaya Mukti; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this research is to find similarities and differences of sharia bank and convenstional bank’s financial systems from bank employee’s perspective.This study use qualitative method with fenomenology approach because it describes the general meaning of several individuals toward their various life experiences related to the concept or phenomenon.. The data used in this research are primary data that obtained through in-depth interview with bank employee and secondary data that obtained form of documentation study to be done triangulation data. The main focus in this study is describe what are the similarities and differences of financial system in sharia bank and conventional bank of what is happening in the reality. The results of this study indicate that the similarity of financial system is drawn from the experience of bank employees who have worked in sharia and conventional banks derived from the type of product and its function as a financial institution. Meanwhile, the difference of sharia and conventional banks derived from the profit taking and system.In reality, sharia and conventional banks are different in terms of religion point of view, while the contracts and the economic substance of those two banks are the same.Keywords: financial system, sharia bank, conventional bank, bank employeeREFFERENCESAntonio, Muhammad Syafi’i. 2001. Bank Syariah: Dari Teori ke Praktik. Jakarta. Gema Insani.Arif, M. Nur Rianto Al. 2015. Pengantar Ekonomi Syariah Teori dan Praktik. Bandung: CV Pustaka Setia.Bungin, Burhan. 2015. Metodologi Penelitian Sosisal dan Ekonomi: Format Format Kuantitatif dan Kualitatif untuk Studi Sosiologi, Kebijakan Publik, Komunikasi, Manajemen, dan Pemasaran. Jakarta: Prenadamemdia Group.Chong, Beng Soon dan Ming-Hua Liu. 2009. Islamic Banking: Interest-free or Interest-based?. Pasific-Basin Finance Journal, Vol. 14.Creswell, John W. 2015. Penelitian Kualitatif & Desain Riset Memilih di Antara Lima Pendekatan. Edisi Ketiga. Yogyakarta: Pustaka Pelajar.Dewi, Yannani Mutiara. 2018.Perbandingan Bisnis Model, Stabilitas, Serta Kinerja Keuangan Bank Umum Syariah dan Bank Umum Konvensional di Indonesia Periode 2012 - 2016. Universitas Airlangga: Skripsi Tidak Diterbitkan.Hanif, Muhammad. 2016. Economic substance or legal form: an evaluation of Islamic finance practic. International Journal of Islamic and Middle Eastern Finance and Management, Vol. 9 , No. 2.Hasan, Zulkifli Bin. 2016. From legalism to value-oriented Islamic finance practices. Humanomics, Vol. 32, No. 4. Hermansyah. 2008. Hukum Perbankan Nasional Indonesia. Jakarta: Prenada Media Group.Huda, Nurul dan Mohamad Heykal. 2010. Lembaga Keuangan Islam: Tianjauan Teoritis dan Praktis. Edisi Pertama. Jakarta: Kencana Prenada Group.Ismail. 2012. Model Bisnis Perbankan Syariah. Kajian Direktorat Perbankan Syariah Bank Indonesia.Karim, Adiwarman. 2014. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: Raja Grafindo Persada. Kasmir. 2010. Dasar-dasar Perbankan. Jakarta: Rajawali Pers.Kasmir. 2010. Manajemen Perbankan. Jakarta: Rajawali Pers.Kholvadia, Faatima. 2017. Islamic Banking in South Africa – Form Over Substance?. Meditari Accountancy Research, Vol. 24, No.1.Kuswarno, Engkus. 2013. Metode Penelitian Komunikasi Fenomenologi Konsepsi, Pedoman, dan Contoh Penelitiannya. Bandung: Widya Padjadjaran.Latumaerissa, Julius R. 2012. Bank dan Lembaga Keuangan Lain. Jakarta: Salemba Empat.Mardani. 2015. Aspek Hukum LembagaKeuangan Syariah di Indonesia. Edisi Pertama. Jakarta: Prenadamedia Group.Muhamad. 2016. Manajemen Pembiayaan Bank Syariah. Edisi Kedua. Yogyakarta: UPP STIM YKPN.Shihab, M. Quraish. 2002. Tafsir Al-Misbah Pesan, Kesan dan Keserasian Al – Qur’an. Vol. 1. Jakarta Pusat: Lentera Hati Jakarta: Raja Grafindo Persada.Sudarsono, Heri. 2003. Bank & Lembaga Keuangan Syari’ah Deskripsi dan Ilustrasi. Yogyakarta: Ekonisia.Sugiyono. 2015. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Suratno, Thomas dkk. 2005. Kelembagaan Perbankan. Edisi Ketiga. Jakarta: Percetakan PT SUN.Umam, Khotibul. 2017. Perbankan Syariah: Dasar-Dasar dan Dinamika Perkembangannya di Indoensia. Depok: PT Rajagrafindo Persada.Usman, Rachmadi. 2012. Aspek Hukum Perbankan Syariah di Indonesia. Jakarta: Sinar Grafika.Yusuf, Muri. 2014. Metode Penelitian: Kuantitatif, Kualitatif, dan Penelitian Gabungan. Edisi Pertama. Jakarta: Prenadamedia Group.